Stabilized piezoelectricity upon ferro-ferro phase transition achieved by aging induced domain memory effect in acceptor doped lead-free ceramics. (October 2022) - Yin, Mengye; Fang, Minxia; Ji, Yuanchao; Wang, Dong; Ren, Xiaobing
Abstract: Strong temperature dependence of piezoelectricity ( d 33 ) attributed to morphotropic/polymorphic transition at room temperature limits the practical application of high performance lead-free piezoceramics. This work found aging induced domain memory effect is effective stabilizing d 33 through ferroelectric orthorhombic (O)-tetragonal (T) transition together with a large room temperature d 33 ( d 33@RT ) in Mn doped lead-free 55Ba(Ti0.8 Zr0.2 )O3 -45(Ba0.7 Ca0.3 )TiO3 piezoceramics: 23.2% d 33 variation through O-T transition and a large d 33@RT ∼ 323 pC/N for doped one when compared with those of undoped one (96.8% d 33 variation and d 33@RT ∼ 278 pC/N). Restoring force induced by defect dipoles according to the symmetry conforming short-range ordering principle has been demonstrated with internal bias field and double hysteresis loops, while the outcoming domain memory effect, responsible for the stabilized behaviors, has been revealed with transmission electron microscopy observation and phase-field simulation. Thus, aging induced domain memory effect is effective achieving stabilized behaviors and large d 33@RT simultaneously. Graphical abstract: Image, graphical abstract